Kepuasan Pelanggan pada Perusahaan Logistik di Indonesia - Kadarisman, Muh; As'siddiq, Imam Bahdi; Nofrisel, Nofrisel; Simarmata, Juliater; Saputra, Candra Mardhika (Institut Transportasi dan Logistik Trisakti, 2024)
The main problem of the research was the deficient in operational risk control of marine exports at Kintetsu World Express Indonesia. Risk control is an integral part of management's responsibility to ensure the achievement of organizational goals. This research consists of independent variables, namely risk management and operational performance, as well as mediating variable, namely service quality, and the dependent variable, namely customer satisfaction. This research aims to analyze the influence of risk management and operational performance through service quality, simultaneously or partially, and directly or indirectly, on customers’ satisfaction at one of the Logistics’ companies in Indonesia. All users of cargo delivery services, 30 respondents, at Kintetsu World Express Indonesia in 2021 were taken as samples. Hypothesis testing was carried out using Path analysis method. The results of hypothesis testing carried out on Model-1 structure show that simultaneously the risk management variable and operational performance have a positive and significant effect. The results of hypothesis testing carried out on Model-2 structure show that simultaneously the service quality variable has a positive and significant effect on customer’s satisfaction.